2022
DOI: 10.3390/cells11192957
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and Functional Analysis of a New Nuclear Localization Sequence of the Influenza A Virus Nucleoprotein

Abstract: Influenza viruses deliver their genome into the nucleus of infected cells for replication. This process is mediated by the viral nucleoprotein (NP), which contains two nuclear localization sequences (NLSs): NLS1 at the N-terminus and a recently identified NLS2 (212GRKTR216). Through mutagenesis and functional studies, we demonstrated that NP must have both NLSs for an efficient nuclear import. As with other NLSs, there may be variations in the basic residues of NLS2 in different strains of the virus, which may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…These results indicate that the NLS2MT virus spread slower and was less infectious than the NLS1MT virus. This difference may be due to the role of NLS2 in the nucleolar localization of NP because, in transfected cells, NLS2 significantly promotes the nuclear import of NP to the same extent as NLS1 [ 18 ]. Hence, a dysfunctional NLS2 affects the infectious cycle of the influenza A virus more dramatically than a mutated NLS1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results indicate that the NLS2MT virus spread slower and was less infectious than the NLS1MT virus. This difference may be due to the role of NLS2 in the nucleolar localization of NP because, in transfected cells, NLS2 significantly promotes the nuclear import of NP to the same extent as NLS1 [ 18 ]. Hence, a dysfunctional NLS2 affects the infectious cycle of the influenza A virus more dramatically than a mutated NLS1.…”
Section: Discussionmentioning
confidence: 99%
“…NLS2 was first proposed to be a classical bipartite NLS [ 17 ], but site-directed mutagenesis and crystallographic studies have defined it as monopartite NLS at residues 212–214 ( 212 GRKTR 216 ) that predominantly binds to the importin-α major NLS-binding site [ 13 ]. A recent bioinformatics study found NLS2 to be highly conserved among different influenza A strains, with 67.6% of strains containing 212 GRKTR 216 and 31.2% with the sequence 212 GRRTR 216 [ 18 ]. Performing competition of the nuclear import of NP during infection with chimeric proteins containing NLS1 or NLS2, it was demonstrated that both NLS1 and NLS2 are indispensable for influenza infection [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations